FACTORS ENCOURAGING EARLY MARRIAGE AMONG ADOLESCENT GIRLS IN EAST JAVA OF INDONESIA - kasiati kasiati; Dina Isfentiani (AIPKIND (Asosiasi Pendidikan Kebidanan Indonesia), 2020)
Early marriages occur in Indonesia and this still contributes to maternal and child mortality. Therefore, research is needed to find out the reasons why the incidence of early marriage can occur. This research was conducted in four sub-districts in Surabaya, East Java, Indonesia, by taking respondents based on the technique of snowball sampling. After the interview, several factors had apparently contributed to this early marriage, among others, culture, economic level, level of education, and level of knowledge on marriage. This of course requires a program to increase the age of first marriage by a woman called maturing marriage age. It is hoped that the contributing factors to early marriage will not be repeated in the future when the perpetrators of the early marriage are given an explanation of the importance of delaying the age of marriage to adulthood.